2018
DOI: 10.1021/acs.analchem.7b04375
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Doubly Activated Dual Emission Fluorescent Probes for Selective Imaging of Glutathione or Cysteine in Living Systems

Abstract: The development of novel fluorescent probes for monitoring the concentration of various biomolecules in living systems has great potential for eventual early diagnosis and disease intervention. Selective detection of competitive species in biological systems is a great challenge for the design and development of fluorescent probes. To improve on the design of fluorescent coumarin-based biothiol sensing technologies, we have developed herein an enhanced dual emission doubly activated system (DACP-1 and the clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(49 citation statements)
references
References 52 publications
(69 reference statements)
0
47
0
2
Order By: Relevance
“…Thus the conclusion was reached that the E1 probe is useful for fluorogenic detection of Hg(ii) over a relatively wide pH range of pH 4-11. Changes in the fluorescence emission spectra of the E1 probe (20 µmol/L) upon addition of different amounts of Hg(ii) (0, 1,2,4,8,12,16,20,40 and 60 µmol/L) were measured ( Figure 5). It was found that with increasing amounts of Hg(ii) added to E1 that the intensity of the fluorescence emission band at 466 nm decreased gradually, and that the intensity of the emission peak at 395 nm increased.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus the conclusion was reached that the E1 probe is useful for fluorogenic detection of Hg(ii) over a relatively wide pH range of pH 4-11. Changes in the fluorescence emission spectra of the E1 probe (20 µmol/L) upon addition of different amounts of Hg(ii) (0, 1,2,4,8,12,16,20,40 and 60 µmol/L) were measured ( Figure 5). It was found that with increasing amounts of Hg(ii) added to E1 that the intensity of the fluorescence emission band at 466 nm decreased gradually, and that the intensity of the emission peak at 395 nm increased.…”
Section: Resultsmentioning
confidence: 99%
“…However, the fluorescence emission spectra of the E1 probe changed in accordance with the nature of each amino acid which was added: Cys, Phe, Asn, Val, His, Glu and Gly all led to a decrease in intensity of the fluorescence emission band at 466 nm. The Changes in the fluorescence emission spectra of probe E1 (20 µmol/L) upon the addition of different amounts of Cys (0, 2,4,6,8,10,12,14,16,18,20 and 40 µmol/L) were measured ( Figure 8). The strongly fluorescent E1 probe gradually turned weakly fluorescent as increasing amounts of Cys were added to E1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the reaction mechanism between probe 1 and Cys/Hcy/GSH, several control compounds (C5‐C9) were synthesized (Supporting Information, Scheme S2), and characterized (Supporting Information, Figures S31–S40). Judging from the LC‐MS and HRMS spectra from the reactions between probe 1 and Hcy/Cys/GSH and the absorption spectra of these control compounds (Supporting Information, Figures S8 and S14–S16), mechanisms were proposed for the reactions between probe 1 and Hcy/Cys/GSH (Supporting Information, Scheme S2) . The isolation of the products of these reactions failed, which may be due to their instability.…”
Section: Methodsmentioning
confidence: 99%